CORPORATE SOCIAL RESPONSIBILITY IN THE HALAL FOOD INDUSTRY: APPLICATION OF SUPPLY CHAIN PERSPECTIVE (International Journal of Islamic Business, 2023)
This study aims to construct a comprehensive framework for Corporate Social Responsibility (CSR) within the Halal food industry's supply chain. It acknowledges the increasing public attention towards corporate social responsibility (CSR) and supply chain practices in the food industry. It utilizes current literature and recent developments to provide a comprehensive understanding of CSR in the Halal context. Methodologically, this study conducts a systematic review of relevant articles and materials, forming a robust theoretical underpinning. Our findings reveal key CSR dimensions specific to the Halal food supply chain, including animal welfare, health and safety, environmental concerns, and community involvement. The proposed framework not only enhances understanding of Halal supply chain CSR practices but also sets the stage for strategic and operational improvements. Significantly, this study contributes to the scholarly conversation by integrating Islamic principles with contemporary CSR practices, offering a unique perspective that aligns business operations with ethical and religious standards.